Response of Agronomic Traits and Phosphorus Uptake to Soil P Deficiency During Rice Cultivars Improvement - Chunqin Li; Xu Mo; Shuwei Li; Yuxi Liu; Rongxin Chen; Shuying Yu; Wenqiang Lin; Yifeng Wang; Yajun Hu (Agronomy)
Developing high phosphorus (P) efficient rice varieties is essential for sustainable phosphate resource conservation. This study evaluated 16 rice cultivars from four breeding eras: ancient (<1940), early conventional (1940–2000), modern conventional (2000–2020), and hybrid rice (2000–2020). Using pot experiments in low-P soil, we examined two P treatments: P0 (no P application, simulating low-P stress) and P50 (50 kg hm−1 P application, normal P input). We systematically compared agronomic traits, P distribution patterns, and P uptake efficiency across breeding generations. The result showed that modern breeding significantly increased root biomass, shoot biomass, and grain yield while reducing plant height. Low-P stress (P0) had minimal impact on growth traits but negatively affected P uptake, particularly plant P content and accumulation patterns. Under P0 treatment, modern conventional varieties maintained a higher stem P concentration (0.47–0.65 g·kg−1 vs. 0.27–0.49 g·kg−1 in hybrid varieties; 0.47–0.65 g·kg−1 vs. 0.18–0.28 g·kg−1 in ancient varieties, p < 0.05). P allocation strategies varied significantly across breeding eras. Root P accumulation ratios decreased from ancient to modern varieties, while modern conventional rice had the highest stem P storage (24.1–30.5%), and hybrid rice allocated the largest partition of 76.4–78.1% P to grains. Additionally, P uptake efficiency and P fertilizer productivity increased by 131.09% and 91.21% (p < 0.01) from ancient to modern conventional rice, with hybrids exhibiting the highest values for both parameters. Principal component analysis (PCA) revealed distinct trait clusters separating ancient, conventional, and hybrid rice based on the agronomic traits, P uptake, and rhizosphere soil parameters. Random forest analysis identified that, under low-P conditions, root P content was the strongest predictor of grain yield, whereas under normal P conditions, rhizosphere pH had the highest relationship to grain yield. These findings demonstrate that modern breeding has enhanced P adaptation through optimized root architecture and organ-specific P allocation strategies, which providing valuable insights for developing future P-efficient rice varieties.